(untitled) - Buxbaum, Yitzhak (San Francisco, 2002)
What is a "holy woman," or a holy man for that matter? According to the Jewish mystics, a holy person is someone who has not lost the holiness that every baby is born with. A holy person is someone who fulfills it. Stories about Jewish holy women have rarely been collected in such an engaging and entertaining form. The tales display a specifically female Jewish spirituality, giving us a peek into a world of devotional beauty that focuses on kindness. These stories of laughter and tears, humility and bravery, striving and trance, have an appeal spanning the denominational spectrum: they are spiritual nourishment for the soul. The rabbis say there are both male and female angels and angels are on earth as well as in heaven. These tales enhance our appreciation of the female angels on earth.
Keywords: Zaddikot,Legends, jewish; Legends